Modeling and design of a voice-coil motor for auto-focusing digital cameras using an electromagnetic simulation software - Hsu, Jhih-Da; Tzou, Ying-Yu (My University, 2007)
This paper presents the modeling of a voice coil motor (VCM) used for the auto-focusing control of a digital camera in applications to high-performance mobile phones. The force constant and its associated back EMF constant of a VCM can be highly nonlinear with the mechanical structure. Conventional modeling technique using the derived flux distribution based on geometrical structure is quite involved and impractical to identify its equivalent parameters. A modeling procedure for a specially designed VCM is developed based on its mechanical structure and used material by using an electromagnetic simulation software - the Ansoft's Maxwell 2D. An iterative optimal design process is then proposed to maximize the force constant of the VCM with a specified volume. Simulation results with experimental verification are given to illustrate that the proposed design procedure can achieve a satisfactory performance.
Keywords: voice coil motor; modeling; electromagnetic simulation; iterative optimal design